The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1007/bf00173646
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antitumor activity of sparsomycin and its analogues in eight murine tumor models

Abstract: Sparsomycin (Sm) is a known inhibitor of ribosomal protein synthesis with an attractive anticancer potential. Recently, several analogues of Sm which are more active than the parent drug were selected for further study on the basis of in vitro investigations. Six analogues as well as the parent drug were tested for their antitumor activity in eight in vivo murine tumor models: P388 and L1210 leukemias, RC renal cell carcinoma, B16 melanoma, C38 colon carcinoma, LL Lewis lung carcinoma, C22LR osteosarcoma and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The difference between the in vitro and in vivo antiplasmodial activity of Sm possibly resulted from its toxicity and rapid metabolic clearance [ 37 , 38 ], which does not allow adequate drug levels to be reached in vivo. A difference between in vitro and in vivo results was also reported for the antitumor activity of Sm [ 22 ].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The difference between the in vitro and in vivo antiplasmodial activity of Sm possibly resulted from its toxicity and rapid metabolic clearance [ 37 , 38 ], which does not allow adequate drug levels to be reached in vivo. A difference between in vitro and in vivo results was also reported for the antitumor activity of Sm [ 22 ].…”
Section: Discussionmentioning
confidence: 88%
“…Although Sm is likely inactive when administered orally to mice [ 7 ], the reported LD 50 of the drug following i.p. administration ranged from 170 to 380 μg/kg per injection in mice and the IC 50 in some murine tumor models varied from 125 to 500 μg/kg [ 22 ]. Accordingly, in this study, mice were treated with i.p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Broad in vivo antitumor testing revealed that 1 was weakly active or inactive, whereas deshydroxy-sparsomycin (58), n-pentyl-sparsomycin (59), and ethyl-deshydroxy-sparsomycin (60) were significantly active in the L1210 and renal cell sarcoma models. 55 Further implications that the peptidyltransferase center where 1 interacts has a hydrophobic core were demonstrated with analogs in which polar groups at the S2-Me site were inactive, whereas S2-alkyl group modification produced lipophilic derivatives with excellent activity in the L1210 leukemia assay in mice in which test/control (T/C) >125 for prolongation of life is considered active. The n-pentyl derivative 59…”
Section: Biology and Sar Of Sparsomycinmentioning
confidence: 99%
“…Amicoumacin A was recently shown to have cytotoxic effects on breast cancer and lung cancer cells, while pactamycin had a cytostatic antitumorigenic effect on head and neck squamous cell carcinomas as a result of the induction of several cell cycle arrest regulatory proteins [ 110 , 111 ]. Sparsomycin, another cytostatic agent, also inhibited the growth of murine leukemia and renal cell carcinomas [ 112 , 113 ]. The most clinically relevant plectin ligand is omacetaxine mepesuccinate that is used to treat patients with chronic myeloid leukemia that are resistant to tyrosine kinase inhibitors [ 114 , 115 , 116 ].…”
Section: Therapeutic Targeting Of Plakinsmentioning
confidence: 99%